Effectiveness of Neurogenesis in treating Children with Cerebral Palsy - AMIRSALARI, Susan; DEHGHAN, Leila; DALVAND, Hamid; HAGHGOO, Hojjat Allah (Iranian Journal of Child Neurology, 2012)
How to Cite this Article: Amirsalary S, Dehghan L, Dalvand H, Haghgoo H. Effectiveness of Neurogenesis in treating children with Cerebral Palsy. Iran J Child Neurol 2012;6(2):1-8. objective Tissue-specific stem cells divide to generate different cell types for the purpose oftissue repair in the adult. The aim of this study was to detect the significance ofneurogenesis in the central nervous system in patients with cerebral palsy (CP). Materials & Methods A search was made in Medline, CINAHL, PubMed, ISI Web of Science andGoogle Scholar from 1995 to February 2011. The outcomes measured in thereview were classified to origins, proliferation, and migration of new neurons,and neurogenesis in CP. Results According to the review of articles, neurogenesis persists in specific brainregions throughout lifetime and can be enhanced from endogenous progenitorcells residing in the subventricular zone by growth factors or neurotrophicfactors and rehabilitation program. Conclusion Most of the studies have been conducted in the laboratory and on animals,more work is required at the basic level of stem cell biology, in the developmentof human models, and finally in well-conceived clinical trials. References 1. Buonomano DV, Merzenich MM. Cortical plasticity: from synapses to maps. Annu Rev Neurosci 1998; 21:149-86. 2. Haghgoo H. Fundemental of neurosciences. 1st ed. Tehran; USWR Press; 2011. 3. Payne BR, Lomber SG. Reconstructing functional systems after lesions of cerebral cortex. Nat Rev Neurosci 2001 Dec;2(12):911-9. 4. Bax M, Goldstein M, Rosenbaum P, Leviton A, Paneth N, Dan B, et al. Proposed definition and classification of cerebral palsy. Dev Med Child Neurol 2005 Apr;47(8):571-6. 5. Joghataei M, Kazem M. Barresi sathe niazhaie jamee be khadamate behzisti colle keshvar [persian].Tehran: University of. Social Welfare and Rehabilitation Sciences; 1990. 6. Johnson A. Prevalence and characteristics of children with cerebral palsy in Europe. Dev Med Child Neurol 2002 Sep;44(9):633-40. 7. Yeargin-Allsopp M, Van Naarden Braun K, Doernberg NS, Benedict RE, Kirby RS, Durkin MS. Prevalence of cerebral palsy in 8-year-old children in three areas of the United States in 2002: a multisite collaboration. Pediatrics 2008 Mar;121(3):547-54. 8. Uvebrant P. Hemiplegic cerebral palsy. Aetiology and outcome. Acta Paediatr Scand Suppl 1988;345:1-100. 9. Marin-Padilla M. Developmental neuropathology and impact of perinatal brain damage. II: white matter lesions of the neocortex. J Neuropathol Exp Neurol 1997 Mar;56(3):219-35. 10. Tzarouchi LC, Astrakas LG, Zikou A, Xydis V, Kosta P, Andronikou S, et al. Periventricular leukomalacia in preterm children: assessment of grey and white matter and cerebrospinal fluid changes by MRI. Pediatr Radiol 2009 Dec;39(12):1327-32.11. Dehghan L, Dalvand H. Neuroplasticity after stroke [persian]. Modern rehabilitation 2008;1(4). 12. Sanai N, Tramontin AD, Quiñones-Hinojosa A, Barbaro NM, Gupta N, Kunwar S, et al. Unique astrocyte ribbon in adult human brain contains neural stem cells but lacks chain migration. Nature 2004 Feb;427(6976):740-4. 13. Doetsch F, Garcia-Verdugo JM, Alvarez-Buylla A. Cellular composition and three-dimensional organization of the subventricular germinal zone in the adult mammalian brain. J Neurosci 1997 Jul 1;17(13):5046-61. 14. Laywell ED, Rakic P, Kukekov VG, Holland EC, Steindler DA. Identification of a multipotent astrocytic stem cell in the immature and adult mouse brain. Proc Natl Acad Sci U S A 2000 Dec 5;97(25):13883-8. 15. Seri B, Garcia-Verdugo JM, McEwen BS, AlvarezBuylla A. Astrocytes give rise to new neurons in the adult mammalian hippocampus. J Neurosci 2001 Sep 15;21(18):7153-60. 16. Seri B, Garcia-Verdugo JM, Collado-Morente L, McEwen BS, Alvarez-Buylla A. Cell types, lineage, and architecture of the germinal zone in the adult dentate gyrus. J Comp Neurol 2004 Oct 25;478(4):359-78. 17. Sugiura S, Kitagawa K, Tanaka S, Todo K, OmuraMatsuoka E, Sasaki T, et al. Adenovirus-mediated gene transfer of heparin-binding epidermal growth factor-like growth factor enhances neurogenesis and angiogenesis after focal cerebral ischemia in rats. Stroke 2005 Apr;36(4):859-64. 18. Ellsworth JL, Garcia R, Yu J, Kindy MS. Fibroblast growth factor-18 reduced infarct volumes and behavioral deficits after transient occlusion of the middle cerebral artery in rats. Stroke 2003 Jun;34(6):1507-12. 19. Wada K, Sugimori H, Bhide PG, Moskowitz MA, Finklestein SP. Effect of basic fibroblast growth factor treatment on brain progenitor cells after permanent focal ischemia in rats. Stroke 2003 Nov;34(11):2722-8. 20. Baldauf K, Reymann KG. Influence of EGF/bFGF treatment on proliferation, early neurogenesis and infarct volume after transient focal ischemia. Brain Res 2005 Sep 21;1056(2):158-67. 21. Chmielnicki E, Benraiss A, Economides AN, Goldman SA. Adenovirally expressed noggin and brain-derived neurotrophic factor cooperate to induce new medium spiny neurons from resident progenitor cells in the adult striatal ventricular zone. J Neurosci 2004 Mar 3;24(9):2133-42. 22. Cho SR, Benraiss A, Chmielnicki E, Samdani A, Economides A, Goldman SA. Induction of neostriatal neurogenesis slows disease progression in a transgenic murine model of Huntington disease. J Clin Invest 2007 Oct;117(10):2889-902. 23. Gonzalez-Perez O, Jauregui-Huerta F, GalvezContreras AY. Immune system modulates the function of adult neural stem cells. Curr Immunol Rev 2010 Aug 1;6(3):167-73. 24. Doetsch F, Alvarez-Buylla A. Network of tangential pathways for neuronal migration in adult mammalian brain. Proc Natl Acad Sci 1996 Dec 10;93(25):14895-900. 25. Weickert CS, Webster MJ, Colvin SM, Herman MM, Hyde TM, Weinberger DR, et al. Localization of epidermal growth factor receptors and putative neuroblasts in human subependymal zone. J Comp Neurol 2000 Jul 31;423(3):359-72. 26. Magavi SS, Leavitt BR, Macklis JD. Induction of neurogenesis in the neocortex of adult mice. Nature 2000 Jun 22;405(6789):951-5. 27. Lois C, Garcia-Verdugo JM, Alvarez-Buylla A. Chain migration of neuronal precursors. Science. 1996 Feb 16;271(5251):978-81. 28. Wichterle H, Garcia-Verdugo JM, Alvarez-Buylla A. Direct evidence for homotypic, glia-independent neuronal migration. Neuron 1997 May;18(5):779-91. 29. Lois C, Alvarez-Buylla A. Long-distance neuronal migration in the adult mammalian brain. Science 1994 May 20;264(5162):1145-8. 30. Mason HA, Ito S, Corfas G. Extracellular signals that regulate the tangential migration of olfactory bulb neuronal precursors: inducers, inhibitors, and repellents. J Neurosci 2001 Oct 1;21(19):7654-63. 31. Lundy-Ekman L. Neuroscience: fundamentals for rehabilitation. 3rd ed. Philadelphia: WB Saunders; 2007. 32. Mizuno K, Hida H, Masuda T, Nishino H, Togari H. Pretreatment with low doses of erythropoietin ameliorates brain damage in periventricular leukomalacia by targeting late oligodendrocyte progenitors: a rat model. Neonatology 2008;94(4):255-66. 33. Lin S, Fan LW, Pang Y, Rhodes PG, Mitchell HJ, Cai Z. IGF-1 protects oligodendrocyte progenitor cells and improves neurological functions following cerebral hypoxia-ischemia in the neonatal rat. Brain Res 2005 Nov 23;1063(1):15-26. 34. Gonzalez FF, Abel R, Almli CR, Mu D, Wendland M, Ferriero DM. Erythropoietin sustains cognitive function and brain volume after neonatal stroke. Dev Neurosci 2009;31(5):403-11. 35. Goldman SA. Adult neurogenesis: from canaries to the clinic. J Neurobiol 1998 Aug;36(2):267-86. 36. Tureyen K, Vemuganti R, Bowen KK, Sailor KA, Dempsey RJ. EGF and FGF-2 infusion increases post ischemic neural progenitor cell proliferation in the adult rat brain. Neurosurgery 2005 Dec;57(6):1254-63; discussion -63. 37. Im SH, Yu JH, Park ES, Lee JE, Kim HO, Park KI, et al. Induction of striatal neurogenesis enhances functional recovery in an adult animal model of neonatal hypoxic-ischemic brain injury. Neuroscience 2010 Aug 11;169(1):259-68. 38. Greenough WT, Black JE, Wallace CS. Experience and brain development. Child Dev 1987 Jun;58(3):539-59.39. Daadi MM, Davis AS, Arac A, Li Z, Maag AL, Bhatnagar R, et al. Human neural stem cell grafts modify microglial response and enhance axonal sprouting in neonatal hypoxic-ischemic brain injury. Stroke 2010 Mar;41(3):516-23. 40. Lee JA, Kim BI, Jo CH, Choi CW, Kim EK, Kim HS, et al. Mesenchymal stem-cell transplantation for hypoxic-ischemic brain injury in neonatal rat model. Pediatr Res 2010 Jan;67(1):42-6. 41. Yasuhara T, Matsukawa N, Yu G, Xu L, Mays RW, Kovach J, et al. Behavioral and histological characterization of intrahippocampal grafts of human bone marrow-derived multipotent progenitor cells in neonatal rats with hypoxic-ischemic injury. Cell Transplant 2006;15(3):231-8. 42. van Velthoven CT, Kavelaars A, van Bel F, Heijnen CJ. Repeated mesenchymal stem cell treatment after neonatal hypoxia-ischemia has distinct effects on formation and maturation of new neurons and oligodendrocytes leading to restoration of damage, corticospinal motor tract activity, and sensorimotor function. J Neurosci 2010 Jul 14;30(28):9603-11. 43. Chopp M, Li Y, Zhang ZG. Mechanisms underlying improved recovery of neurological function after stroke in the rodent after treatment with neurorestorative cellbased therapies. Stroke 2009 Mar;40(3 Suppl):S143-5. 44. Buhnemann C, Scholz A, Bernreuther C, Malik CY, Braun H, Schachner M, et al. Neuronal differentiation of transplanted embryonic stem cell-derived precursors in stroke lesions of adult rats. Brain 2006 Dec;129(Pt 12):3238-48. 45. Daadi MM, Lee SH, Arac A, Grueter BA, Bhatnagar R, Maag AL, et al. Functional engraftment of the medial ganglionic eminence cells in experimental stroke model. Cell Transplant 2009;18(7):815-26. 46. van Velthoven CT, Kavelaars A, van Bel F, Heijnen CJ. Regeneration of the ischemic brain by engineered stem cells: fuelling endogenous repair processes. Brain Res Rev 2009 Jun;61(1):1-13. 47. Qu R, Li Y, Gao Q, Shen L, Zhang J, Liu Z, et al. Neurotrophic and growth factor gene expression profiling of mouse bone marrow stromal cells induced by ischemic brain extracts. Neuropathology 2007 Aug;27(4):355-63. 48. Li Y, Chopp M. Marrow stromal cell transplantation in stroke and traumatic brain injury. Neuroscience Letters 2009; 456 (3): 120-123.